The concept of a world economic order - Horst Siebert (Kiel Institute for the World Economy (IfW), 2008)
This paper studies the concept of an international economic order, i.e. an institutional arrangement of international rules. Such rules emerge from negative experiences – historical disasters – that inflict severe hardship on people. A taxonomy for rules reducing transaction costs is developed, for instance through decentralization of decisions, property rights, territoriality and the internalization of border-crossing negative externalities and mechanisms for global public goods. Some aspects of the rule system are studied including the process of ceding sovereignty and philosophical thoughts on international rules.
Keywords: A12; F02; F15; K00; N00; P00; 330; Transaction costs; Welfare gains of rules; Property rights; Hierarchy of rules; Concept of order; Freiburg school; International rules; Weltwirtschaftsordnung; Internationales Wirtschaftsrecht; Transaktionskosten; Wohlfahrtseffekt; Ordoliberalismus; Welt